The phantom tollbooth. - Juster, Norton, 1929-; Feiffer, Jules (New York, Epstein & Carroll; distributed by Random House, 1961)
A journey through a land where Milo learns the importance of words and numbers provides a cure for his boredom.
Keywords: Fantasy